Diaquabis[5-(2-pyridylmethyl)tetrazolato-κ(2) N (1),N (5)]manganese(II) - Wang, Wei (International Union of Crystallography, 2008)
The title complex, [Mn(C(7)H(6)N(5))(2)(H(2)O)(2)], was obtained by the in situ hydrothermal reaction of MnCl(2) with 2-(2-pyridyl)acetonitrile in the presence of NaN(3). The Mn(II) atom, which is located on an inversion centre, has a distorted octahedral coordination geometry formed by two water molecules and two chelating ligands. Intermolecular hydrogen bonds and π–π interactions (3.452 Å) stabilize the crystal structure and lead to the formation of a three-dimensional network.